1997
DOI: 10.1097/00004647-199701000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Infusion of Adrenomedullin and Increase in Regional Cerebral Blood Flow and Prevention of Ischemic Brain Injury after Middle Cerebral Artery Occlusion in Rats

Abstract: The intravenous infusion of rat adrenomedullin, at concentrations ranging from 0.1 to 1.0 microgram/kg/min, for 60 min increased the regional cerebral blood flow (rCBF) in a dose-dependent manner in rats. rCBF was measured using a laser Doppler flowmetry device placed on the surface of the parietal cortex. The increase in rCBF induced by 1.0 microgram/kg/min of adrenomedullin was up to 145 +/- 10.8% of controls at 60 min (n = 5, p < 0.001). These concentrations of adrenomedullin did not affect systemic blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 19 publications
1
52
0
Order By: Relevance
“…A previous study by Dogan et al (31) showed that infusion of 1.0 μg/kg/min of rat AM alone for 2 hours (that is, the total dose of AM is 120 μg/kg BW) starting at 1 hour before the induction of D 1 7 ( 9 -1 0 ) 1 0 7 5 -1 0 8 Figure 5. Effects of human AM/AMBP-1 on morphologic photomicrography of the brain after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Dogan et al (31) showed that infusion of 1.0 μg/kg/min of rat AM alone for 2 hours (that is, the total dose of AM is 120 μg/kg BW) starting at 1 hour before the induction of D 1 7 ( 9 -1 0 ) 1 0 7 5 -1 0 8 Figure 5. Effects of human AM/AMBP-1 on morphologic photomicrography of the brain after stroke.…”
Section: Discussionmentioning
confidence: 99%
“…ADM causes relaxation of rat cerebral arterioles (Nishimura & Suzuki 1997) and has been shown to limit ischaemic brain injury following cerebral artery occlusion in rats (Dogan et al 1997). The site of production of most ADM is endothelial cells, and it seems highly probable that ADM acts in a paracrine manner on vascular smooth muscle cells (VSMCs) to increase local blood flow around areas of ischaemic tissue, where the presence of a non-desensitising receptor would ensure that the vasodilatory signal would not be lost or attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenomedullin has been identified in a variety of tissues, including the CNS, and adrenomedullin-like immunoreactivity has been also described in human cerebrospinal fluid (9). More recently, it has been reported that adrenomedullin also exerts vasodilator activity in the cerebral circulation (10,11) and that this peptide is involved in the regulation of systemic and local blood flow during neonatal cardiovascular adaptation (12, 13) and during birth stress (14). In human fetuses, there is evidence that adrenomedullin participates in cerebral fetal hemodynamic modifications (15).…”
mentioning
confidence: 99%